Know what drives the adoption of climate-smart agriculture across different scales - Läderach, Peter R.D.; Mwongera, Caroline; Lamanna, Christine; Acosta, Mariola; Ampaire, Edidah L.; Eitzinger, Anton; Mwungu, Chris Miyinzi; Shikuku, Kelvin Mashisia; Twyman, Jennifer; Winowiecki, Leigh Ann (International Center for Tropical Agriculture, 2017)
Recognizing successful climate-smart agricultural (CSA) practices is not enough for them to be adopted at scale.